KEMAMPUAN TEMPURUNG KELAPA SEBAGAI PANEL AKUSTIK REFUSER (RESONATOR - DIFUSER) DALAM MENYERAP DAN MENGISOLASI BUNYI - Susilo Indrawati; S Suyatno; Lila Yuwana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
One of requirements of proper hearing condition in a auditorium is the presence of uniform sound distribution. The uniform sound distribution can be achieved by using additional reflectors. However, the addition of reflectors in wide room, such as auditorium, leads to undesirable echoes. Echoescan could be improved by adding absorbent materials. The consequence of this is an emerge of various sound distribution. Therefore, this article performs the combination of two functions of a material, i.e as resonator and diffuser (also known as ‘refuser’). Coconut shells are cut into rectangles with a size of 3cm x 3cm, and also given holes in the middle of about 1 mm and arranged into mosaic. Then, mosaic is combined with Rockwool to be a refuser. The tests involve two types of measurements, i.e determining the value of the absorption coefficient (α) and noise reduction (NR). These test method uses the impedance tube method to determine the ability of the refuser to absorb and isolate the sound. The results shows that the addition of the mosaic (coconut shells) is able to double the value of α to 0.64 at a frequency of 250 Hz. In other words, the refuser could behave as a resonator. Furthermore, the refuser is able to increases the NR value at frequencies above 1000 Hz (30-40 dB) and also able to be used as absorber sound at low frequency (250 Hz) and in higher frequencies (≥ 1000 Hz).